Determination of Manganese in Welded Joint and Pipe Body of API X100 Grade SAWH and SAWL Pipe for Gas Pipeline Transportation Systems - Shao, Xiaodong; Han, Xinli; Song, Guangsan; He, Xiaodong; Liu, Yangqin; Zhu, Jinlian; Wu, Xiaohua (Asian Journal of Chemistry, 2013)
With the rapid development of economy, the demands of oil and gas are further increased. Pipeline system is the main form of transportation for natural gas. The high strength pipe line steels will become the preferred materials for modern natural gas transmission pipeline. It was well known that manganese is an important element in the high strength pipe line steels. In this paper, a simple spectrophotometric method was described for the determination of manganese in X100 grade submerged-arc welding longitudinal steel pipe. The method was based on the oxidation-reduction reaction between ammonium persulphate and manganese(II) producing manganese(VII) in the presence of silver nitrate as a catalyst. The characteristic wavelength of maximum absorption of manganese(VII) was obtained locating at 530 nm. Under the optimum reaction conditions the absorption value was proportional to the concentration of manganese in the range of 0.18-2.0 % (R2 = 0.9997) and the relative standard deviation was less than 3.0 % (n = 5). The proposed method was applied successfully to determine manganese in welded joint and pipe body of X100 grade submerged-arc welding helical and submerged-arc welding longitudinal steel pipe samples.